First evidence that the antimalarial drug artesunate inhibits invasion and in vivo metastasis in lung cancer by targeting essential extracellular proteases - Rasheed, Suhail Ahmed Kabeer; Efferth, Thomas; Asangani, Irfan A.; Allgayer, Heike (International journal of cancer, 2010)
Despite progress in treatment, progressive non-small cell lung cancer (NSCLC) still limits survival dramatically, and novel therapeutic compounds are needed. Initial investigations suggest that artesunate (ART), an antimalarial drug, has antiproliferative capacities. However, antiinvasive and antimetastatic properties of ART in cancer have never been explored. Therefore, this first study was performed to (i) investigate if ART is able to inhibit invasion and metastasis in NSCLC and (ii) to identify first molecular targets and mechanisms mediating this ability. ART significantly impaired matrigel invasion of 6 NSCLC cell lines and inhibited urokinase-type plasminogen activator (u-PA) activity, -protein and -mRNA expression. Furthermore, in a PCR-metastasis array, ART inhibited the expression of several matrix metalloproteinases (MMPs), especially MMP-2 and MMP-7 mRNA/protein. In luciferase reporter assays, ART downregulated MMP-2-, MMP-7- and u-PA-promoter/-enhancer activity, in parallel to AP-1- and NF-kB-transactivation. Si-RNA knockdown of u-PA, MMP-2 and MMP-7 abolished ART's ability to inhibit invasion, confirming their role as essential mediators. In vivo, ART significantly impaired primary tumor growth and metastasis in the chicken embryo metastasis (CAM) model. In conclusion, this is the first study to show that ART considerably suppresses invasion and metastasis in NSCLC, specifically targeting transcription of u-PA, MMP-2 and MMP-7, prompting immediate studies on ART as a novel therapeutic in NSCLC.
Gesehen am 10.05.2023